Visual Function In Ethambutol Induced Optic Neuropathy At a Tertiary Eye Centre: A Retrospective Study: - Sitaula, Sanjeeta; Shah, Chiranjiwi Prasad; Dahal, Hiranath; Dahal, Manisha; Sharma, Ananda Kumar (Birat Journal of Health Sciences, 2025)
Introduction: Ethambutol is an important and widely used drug in the treatment of both tubercular and non-tubercular mycobacterial disease as it is the least toxic of the first line antituberculosis drugs. The main disadvantage of this drug is its associated ocular toxicity, manifesting as optic neuropathy. Objectives: To describe the demography, risk factors and visual function in Ethambutol induced Optic Neuropathy (EON) among patients presenting at a tertiary eye centre in Nepal. Methodology: This retrospective study was conducted at B.P. Koirala Lions Centre for Ophthalmic Studies, Institute of Medicine, where all consecutive patients with ethambutol induced optic neuropathy presenting from 1st April 2022 to 30th March 2024 were recorded. Parameters recorded were patient demographics (age, gender and ethnicity), presenting complaints, duration and dosages of ethambutol, body weight, visual acuity, colour vision, contrast sensitivity and visual field. Results: There were 14 patients (28 eyes) of ethambutol induced optic neuropathy. The mean age of patients taking ethambutol was 50.64± 15.8 years with mean daily dose of 18.27 ± 2.29 mg/kg per day. Bilateral ocular involvement was seen with visual acuity ranging from CFCF to 20/60 in one or both eyes. The most common color vision defect was nonspecific defect seen in six patients. The most common visual field defect was centrocecal scotoma in six cases. Mean contrast sensitivity was 1.50±0.32 log units. Thinning of the RNFL and GCC were seen in all cases of EON and the thinning correlated with the severity of visual loss. Conclusions: EON was seen at a mean dose of 18.27mg/kg and mean duration of 7.25 months with moderate to severe visual loss and decrease in contrast sensitivity and visual field defects. Average RNFL thinning and GCC thinning correlated with the severity of visual loss seen in EON subjects. Awareness and early diagnosis can help reduce the unnecessary blindness due to this condition in the susceptible group.